The MUSICA IASI CH 4 and N 2 O products and their comparison to HIPPO, GAW and NDACC FTIR references - O. E. García; M. Schneider; B. Ertl; E. Sepúlveda; C. Borger; C. Diekmann; A. Wiegele; F. Hase; S. Barthlott; T. Blumenstock; U. Raffalski; A. Gómez-Peláez; et al. (Atmospheric Measurement Techniques, 2018)
This work presents the methane (CH 4 ) and nitrous oxide (N 2 O) products as generated by the IASI (Infrared Atmospheric Sounding Interferometer) processor developed during the project MUSICA (MUlti-platform remote Sensing of Isotopologues for investigating the Cycle of Atmospheric water). The processor retrieves CH 4 and N 2 O with different water vapour and water vapour isotopologues (as well as HNO 3 ) and uses a single a priori data set for all the retrievals (no variation in space and time). Firstly, the characteristics and errors of the products are analytically described. Secondly, the products are comprehensively evaluated by comparisons to the following reference data measured by different techniques and from different platforms as follows: (1) aircraft CH 4 and N 2 O profiles from the five HIAPER Pole-to-Pole Observation (HIPPO) missions; (2) continuous in situ CH 4 and N 2 O observations performed between 2007 and 2017 at subtropical and mid-latitude high-mountain observatories (Izaña Atmospheric Observatory and Jungfraujoch, respectively) in the framework of the WMO–GAW (World Meteorological Organization–Global Atmosphere Watch) programme; (3) ground-based FTIR (Fourier-transform infrared spectrometer) measurements made between 2007 and 2017 in the framework of the NDACC (Network for the Detection of Atmospheric Composition Change) at the subtropical Izaña Atmospheric Observatory, the mid-latitude station of Karlsruhe and the Kiruna polar site. The theoretical estimations and the comparison studies suggest a precision for the N 2 O and CH 4 retrieval products of about 1.5–3 % and systematic errors due to spectroscopic parameters of about 2 %. The MUSICA IASI CH 4 data offer a better sensitivity than N 2 O data. While for the latter the sensitivity is mainly limited to the UTLS (upper troposphere–lower stratosphere) region, for CH 4 we are able to prove that at low latitudes the MUSICA IASI processor can detect variations that take place in the free troposphere independently from the variations in the ...